Enhancing Strategic Company Planning Through Marketing Performance Monitoring Applications - Sucihati, Roos Nana; Khotimah, Khusnul; Ismawati, Ismawati; Yuliana, Yuliana; Septiano, Renil (Jurnal Ekonomi, 2024)
In a dynamic business environment, effective strategic planning becomes critical to achieving optimal marketing performance. However, many companies face challenges in effectively managing and evaluating their marketing strategies. Marketing performance monitoring applications (MPMA) offer a solution by providing real-time data that enables quick and precise monitoring, analysis, and adjustment of marketing strategies. This research examines the role of MPMA in improving strategic planning through a literature review and analysis of empirical data from various studies covering various industry sectors. The results show that companies using MPMA can improve their financial performance by optimizing marketing strategies, identifying marketing opportunities, and allocating resources more efficiently. Although there are challenges in MPMA implementation, such as technical integration and resistance to change, the benefits are far greater. With adequate training and management support, companies can overcome these challenges and fully utilize the potential of MPMA to improve their strategic planning and marketing performance. In conclusion, MPMA is an important tool that can help companies become more responsive and adaptive to market changes, providing a significant competitive advantage in an increasingly complex business environment.